MR angiography of cervical fibromuscular dysplasia. - Heiserman, J E; Drayer, B P; Fram, E K; Keller, P J (American Journal of Neuroradiology, 1992)
The authors present examples of cephalic fibromuscular dysplasia (involving five vessels in two patients) using 2-D time-of-flight MR angiography and conventional angiography. Artifacts that can mimic the MR appearance of fibromuscular dysplasia will tend to decrease the sensitivity and specificity of MRA in its detection.